Fibroadenoma of Ectopic Breast Tissue in the Groin – A Rare Disease Entity. (28th October 2020) - Emechebe, D; Alshal, M; Rana, T; Agaronov, M
Abstract: Introduction/Objective: Ectopic breast tissue (EBT) is a well-documented anomaly of the breast and commonly presents along the embryonic milk line extending between the axilla and groin. Reported incidence of accessory breast is 0.4–6% in females. Pathologies developing in an EBT are reported as a rare entity in the literature. Carcinoma is reported as the common pathology followed by inflammation and fibroadenoma Methods: We present a case of 43-year- old female who presented with a painless mass in her right groin for the past year which gradually increased in size. CT abdomen pelvis with contrast showed a 2.2 x 3.0 x 4.4 cm superficial soft tissue mass in the right groin which was suspected to be a lymph node. Further investigation and histopathological report of biopsy showed ectopic breast tissue with admixed chronic inflammation and reactive changes.However, excision of the mass three months later showed showed proloferation of both glandular and stromal elements. Results: The tissue from the biopsy was positive for GATA 3, mammoglobin, GCDFP and CD 10 and the histological features on excision was confirmatory of fibroadenoma. Conclusion: In conclusion, when tumors or nodules are found along the mammary line, the presence of breast tissue should be considered during the investigation. It is clinically wise to evaluate and screen carefully cases of supernumerary breast for any pathology and for any associated urogenital anomalies such as supernumerary kidneys, polycystic kidneys and renal cell adenocaricnoma. In our case, patient had no associated urogenital anomalies and she is on follow up.